Estimating the stressed-strained state of the vertical mounting joint of the cylindrical tank wall taking into consideration imperfections - Suleimenov, Ulanbator; Zhangabay, Nurlan; Abshenov, Khassen; Utelbayeva, Akmaral; Imanaliyev, Kuanysh; Mussayeva, Saule; Moldagaliyev, Arman; Yermakhanov, Myrzabek; Raikhanova, Gulnura (Eastern-European Journal of Enterprise Technologies, 2022)
Based on the use of a multi-level mathematical model, this paper estimates the stressed-strained state of a cylindrical reservoir in the mounting joint and considers the concentration of stresses in the joint zone. The correctness of the selected mathematical model was verified to show that for an engineering assessment of the stressed-strained state of the wall of a cylindrical tank with variable thickness, it is possible to use the ratios for a cylindrical shell with a constant wall thickness. The spread of values is no more than 1 %, which indicates the proper selection of the mathematical model. A numerical assessment of the stressed-strained state in the zone of the mounting joint proved the assumption of significant stress concentrations in the zone and indicated the determining effect exerted on the concentration of stresses by its geometric dimensions. The concentration of stresses in the joint zone of the tank wall was investigated at various sizes in the ANSYS programming environment. The result of calculating the stressed-strained state of the reservoir for various values of the dent parameters f/t and is the constructed polynomials that approximate the stress concentration coefficient Kσ. As a result of the calculations, an interpolation polynomial and an approximating stress concentration coefficient were derived, which could be used to assess the strength, durability, residual life of the tank and to normalize the limiting dimensions of the imperfection of the joint. This paper reports comparative results of the calculations of the stress concentration coefficient depending on the geometric dimensions of the imperfection of the mounting joint in the ANSYS software package, as well as using an interpolation polynomial. The results could be used to assess the strength and residual life of such structures.